A variable sampling interval S2-EWMA control chart for monitoring the process variance. (27th December 2006) - Castagliola, P.; Celano, G.; Fichera, S.; Giuffrida, F.
This paper proposes a Variable Sampling Interval version of the Fixed Sampling Interval S 2 -EWMA control chart developed by Castagliola (2004) and dedicated to the monitoring of the sample variance of a process. In this paper, we explain how the various parameters of this VSI S 2 -EWMA control chart can be computed and how the use of the VSI feature significantly improves the statistical efficiency of FSI S 2 -EWMA chart, thus representing an effective tool in the detection of process out-of-control conditions. An optimal design strategy based on the Average Time to Signal (ATS) is presented and a comparison with the FSI procedure is performed.